2003
DOI: 10.2113/gscanmin.41.3.597
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-Group Minerals in Podiform Chromitites of the Oman Ophiolite

Abstract: Chromitite lenses rich in the platinum-group elements (PGE) have recently been discovered in the deeper part of the mantle section of the northern part of the Oman ophiolite. In terms of stratigraphic level, there are two types of chromitite: Moho transition zone (MTZ) and mantle types. The mantle type can be further classified into two subtypes: PGE-poor and PGE-rich. Platinum-group minerals (PGM) have been mainly observed in the PGE-rich mantle chromitite and, to a lesser extent, in the PGEpoor mantle chromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(43 citation statements)
references
References 37 publications
2
38
0
3
Order By: Relevance
“…The PGEs, especially the IPGE, tend to increase with an increase in both the volume ratio of chromian spinels and their Cr content (e.g. Crocket, 1979;Page et al, 1982a,b;Economou-Eliopoulos, 1986;Leblanc, 1991;Arai et al, 1999;Proenza et al, 1999;Ahmed and Arai, 2003). With attainment of sulfur saturation under magmatic conditions, the PGE, especially the PPGE, will be collected into the immiscible sulfide droplets that eventually may be concentrated as sulfide deposits at a crustal level.…”
Section: Pge Distribution and Fractionationmentioning
confidence: 99%
“…The PGEs, especially the IPGE, tend to increase with an increase in both the volume ratio of chromian spinels and their Cr content (e.g. Crocket, 1979;Page et al, 1982a,b;Economou-Eliopoulos, 1986;Leblanc, 1991;Arai et al, 1999;Proenza et al, 1999;Ahmed and Arai, 2003). With attainment of sulfur saturation under magmatic conditions, the PGE, especially the PPGE, will be collected into the immiscible sulfide droplets that eventually may be concentrated as sulfide deposits at a crustal level.…”
Section: Pge Distribution and Fractionationmentioning
confidence: 99%
“…They are important as geochemical monitors of deep-seated mantle processes that provide us with constraints on the physico-chemical conditions and evolution of mantle lithosphere (Lago et al, 1982;Leblanc and Ceuleneer, 1992;Liipo et al, 1995;Ahmed and Arai, 2002;Ahmed et al, 2001Ahmed et al, , 2005Ahmed et al, , 2009. It is now widely accepted that ophiolitic chromitites are dominated by Ir-subgroup (IPGE = Os, Ir, Ru) and depleted in Pd-subgroup (PPGE = Rh, Pt and Pd) of PGE (Page et al, 1982a,b;Page and Talkington, 1984;Talkington et al, 1984;Augé, 1986;Prichard et al, 1996;Zhou et al, 1998;Ahmed and Arai, 2003). However, Pt-and Pd-rich chromitites have been recently found associated with sulfide-bearing pods in some ophiolite complexes (Corrivaux and LaFlamme, 1990;Prichard and Lord, 1993;Pedersen et al, 1993;Economou-Ellopoulos, 1996;Augé et al, 1998;Prichard et al, 2008a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Pt and Pd minerals are commonly located at the Moho transition zone, either at the uppermost mantle or in the lower cumulates [27], as melts derived from high degrees of partial melting of a fertile mantle ascend, differentiate and impregnate the uppermost mantle region [5,40]. Therefore, it is concluded that the east Othrys ophiolite was located close to the Moho transition zone, at a higher level relative to the west Othrys.…”
Section: Petrogenetic Implicationsmentioning
confidence: 99%
“…Chromitites are one of the major primary host lithologies of platinum-group elements (PGE) and one of the main targets for their exploration [1][2][3][4][5]. Theoretical and experimental results suggest that silicate minerals (e.g., olivine, and pyroxenes) do not significantly contribute to the Ir-and Pd-groups PGE (IPGE: Os, Ir, and Ru; and PPGE: Rh, Pt, and Pd) budget of mantle rocks, despite the fact that they clearly dominate the upper mantle formations (e.g., [6,7]).…”
Section: Introductionmentioning
confidence: 99%